2018
DOI: 10.1002/jemt.23120
|View full text |Cite
|
Sign up to set email alerts
|

The effects of human menstrual blood stem cells‐derived granulosa cells on ovarian follicle formation in a rat model of premature ovarian failure

Abstract: Many studies have reported that human endometrial mesenchymal stem cells (HuMenSCs) are capable of repairing damaged tissues. The aim of the present study was to investigate the effects of HuMenSCs transplantation as a treatment modality in premature ovarian failure (POF) associated with chemotherapy‐induced ovarian damage. HuMenSCs were isolated from menstrual blood samples of five women. After the in vitro culture of HuMenSCs, purity of the cells was assessed by cytometry using CD44, CD90, CD34, and CD45 FIT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 50 publications
0
37
0
Order By: Relevance
“…hMB-MSCs improved hormone secretion in rats with POF (e.g., AMH, FSHR, FST, E2, and P4). hMB-MSC transplantation not only changed ovarian ultrastructure but also improved ovarian function [131].…”
Section: Human Menstrual Blood-derived Mscs Characteristics Of Human mentioning
confidence: 89%
“…hMB-MSCs improved hormone secretion in rats with POF (e.g., AMH, FSHR, FST, E2, and P4). hMB-MSC transplantation not only changed ovarian ultrastructure but also improved ovarian function [131].…”
Section: Human Menstrual Blood-derived Mscs Characteristics Of Human mentioning
confidence: 89%
“…Increased numbers of primary, mature and total ovarian follicle numbers were observed. DiI-labeled MenSC localized to GCs of immature ovarian follicles (Manshadi et al, 2019). Microarray analysis revealed greater similarity between mRNA expression patterns in the ovarian cells posttransplantation and human ovarian tissue than the pre-transplantation pattern in MenSCs, suggesting transdifferentiation into ovarian cells or fusion of MenSCs with murine cells (Liu et al, 2014).…”
Section: Ovarian Function and Reservementioning
confidence: 93%
“…The reparative capacities of MenSCs was exploited to treat premature ovarian failure (POF) in mouse/rat models (Liu et al, 2014;Feng et al, 2019;Manshadi et al, 2019;Yan et al, 2019). Intra-ovarian or intravenous injection of MenSCs reduced apoptosis and restored ovarian function, shown by expression of the ovarian markers, follicle-stimulating hormone receptor (Fshr), inhibin α/β, anti-Müllerian hormone (Amh), Ddx4 and Vegfa, and rising plasma levels of the ovarian hormones, estrogen and progesterone.…”
Section: Ovarian Function and Reservementioning
confidence: 99%
“…Remarkably, some studies have reported a protective role of MenSCs against GCs death in the ovarian interstitium of an animal model of POF. In these studies, MenSCs restored ovarian function [ 80 , 81 ]. It was suggested that this effect is likely mediated by a decrease in the expression of growth arrest and DNA damage inducible beta (GADD45B), a stress sensor involved in cell cycle control, and by an increase in the expression of cell division control 2 (CDC2) and cyclin B1 as cell cycle inducers [ 82 , 83 , 84 , 85 ].…”
Section: Mesenchymal Stem Cells (Mscs)mentioning
confidence: 99%